A refractory castable specially used for industrial silicon refining ladle and preparation method thereof

By developing a refractory castable specifically for industrial silicon refining ladles and optimizing the ratio and composition, the problem of shortened service life of the silicon ladle lining is solved, the thermal shock resistance and erosion resistance are significantly improved, and the service life is extended.

CN118545989BActive Publication Date: 2025-01-21LUOYANG MAGNESIUM ALUMINUM REFRACTORY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411023360.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-01-21
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

The lack of refractory materials specifically used in industrial silicon refining bags in the prior art has resulted in a shortening of the service life of the silicon bag lining and is unable to effectively resist high temperatures, thermal shocks and chemical erosion.

Method used

A refractory castable specially used for industrial silicon refining ladles has been developed. By optimizing the proportion and composition, including refractory aggregates, refractory fine powders, binders, anti-erosion agents and admixtures, the resistance of the silicon ladle linings has been significantly improved. Thermal shock and erosion resistance.

Benefits of technology

It significantly increases the service life of the silicon bag lining, enhances the corrosion resistance to Na2O, B2O3 and other components in industrial silicon slag, and improves thermal shock resistance, ensuring the material's stable performance under harsh working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A refractory castable specially used for industrial silicon refining ladle and its preparation method, belonging to the field of refractory materials, is composed of refractory aggregate, refractory fine powder, binder, anti-corrosion agent and additives, wherein the refractory aggregate is composed of high-quality bauxite homogenous material and sillimanite particles, the refractory fine powder is composed of plate-like corundum powder, kyanite powder and silicon carbide powder, the binder is calcium aluminate cement, the anti-corrosion agent is composed of spherical asphalt, zirconium-containing silicon powder and metallic silicon powder, and the additive is composed of alumina powder, polypropylene fiber and sodium tripolyphosphate. The present invention uses spherical asphalt, silicon carbide, metallic silicon powder, zirconium-containing silicon powder, etc. in combination, which effectively improves the castable's resistance to Na in slag. 2 O.B 2 O 3 The corrosion resistance of other components is improved, thus achieving a good balance in improving the material's mechanical strength, slag corrosion resistance and thermal shock resistance, so that the castable has excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of refractory materials, in particular to a refractory castable specially used for industrial silicon refining ladle and a preparation method thereof. Background Art

[0002] With the development of industries such as chemical, electronics, and photovoltaic power generation, the demand for industrial silicon (or metallic silicon) in related industries is increasing, and the quality requirements for industrial silicon are also getting higher and higher. At present, both domestic and foreign countries use off-furnace refining technology to improve the purity of industrial silicon, that is, the metallic silicon liquid smelted in the mining furnace with more impurities is transferred to the silicon bag container, and the "flux (synthetic slag) + oxygen blowing oxidation" combined refining process is adopted for refining and purification. This process is usually that when the metallic silicon liquid flows out of the ore-heating furnace and is injected into the silicon bag, oxygen blowing refining is first carried out, and the time is generally 1.0-1.5 hours; then slag (flux) is added and oxygen blowing refining is carried out, and the time is about 1.5 hours; finally, the refined industrial silicon liquid is cast into ingots. The advantages of this refining process are simple operation, low processing cost, high impurity removal rate, no pollution to the atmosphere, and good overall effect.

[0003] Industrial silicon refining ladle (abbreviated as silicon ladle) is not only a transfer container for metallic silicon liquid, but also a device for refining and removing impurities from silicon liquid. During the oxygen blowing refining process of industrial silicon, the lining material of the silicon ladle is simultaneously subjected to the combined destructive effects of multiple factors such as high temperature, thermal shock and chemical erosion, and the working conditions are harsh. Due to the lack of refractory materials dedicated to industrial silicon refining ladle, the existing technology generally uses refractory castables used in the field of steel smelting. However, due to the large differences in the working conditions and composition between metallic silicon liquid and molten steel or molten iron, the service life of the existing refractory castables in the steel field will be significantly shortened when they are directly applied to the lining of the silicon ladle. For example, the same refractory material, when used in the field of steel smelting, generally has a service life of 5-6 months, but when it is applied to the lining of the silicon ladle, the service life will generally be reduced to about two months.

[0004] The reasons why the existing refractory castables are used in the silicon ladle lining are shortened are generally considered to be the following two aspects:

[0005] On the one hand, the use of silicon ladle is intermittent, and it is usually used 4 to 6 hours after each use. The temperature of metal silicon liquid is usually above 1700℃, sometimes even close to 1800℃, which is 100℃ to 200℃ higher than the temperature of molten steel. Therefore, the thermal shock to the lining material of the silicon ladle is greater. When the metal silicon liquid flows out of the ore-fired furnace and is injected into the silicon ladle, the initial oxygen blowing refining temperature is generally controlled at above 1600℃, and the later slag (flux) oxygen blowing refining temperature is generally 1520℃ to 1580℃. It can be seen that the lining material of the silicon ladle has to frequently withstand severe thermal shock with a temperature difference of more than 1100℃ and long-term high temperature, especially for new ladle that has just been put into use and has no slag layer attached. The thermal shock it receives when receiving silicon liquid is more severe.

[0006] On the other hand, and more importantly, different slag systems lead to different corrosiveness. At present, there are four main synthetic slag systems for industrial silicon refining, namely, Na2O / B2O3-SiO2 system, SiO2-CaO-Na2O system, CaO-Al2O3-SiO2 system and CaO-CaF2- Fe2O3-SiO2 system. These synthetic slag components react with impurity elements in metal silicon liquid at high temperature to form oxides that enter the silicon slag and corrode the refractory materials of the silicon lining, especially Na2O, B2O3 and other components, which directly contact and react with Al2O3 in the refractory materials to generate low melting point compounds such as Na2O∙11Al2O3 and Al2O3∙B2O3, which cause serious corrosion to the refractory materials. However, since the refined synthetic slag used in steel smelting does not contain Na2O and B2O3 components, the refractory materials used in steel smelting do not take into account the erosion caused by the reaction of Na2O, B2O3 and other materials with the refractory materials. Therefore, when the refractory materials for steel smelting are directly applied to the lining of the silicon bag, it will inevitably lead to a reduction in service life. Summary of the invention

[0007] In order to solve the problem of reduced lining life caused by the lack of dedicated refractory materials in the prior art silicon ladle lining and the use of only refractory castables in the steel field, the present invention provides a refractory castable specifically for industrial silicon refining ladle and a preparation method thereof. The refractory castable of the present invention fully considers the unique corrosiveness of the industrial silicon refining slag system to refractory materials, improves the proportion and composition of the castable from a mechanistic point of view, and thus significantly improves the service life of the silicon ladle lining.

[0008] The technical solution adopted by the present invention to solve the above technical problems is: a refractory castable specially used for industrial silicon refining ladle, which is composed of refractory aggregate, refractory fine powder, binder, anti-corrosion agent and additive. According to the weight ratio, the refractory aggregate is composed of 61-68.5 parts of high-quality bauxite homogenous material and 2.5-4 parts of sillimanite particles, the refractory fine powder is composed of 5-8 parts of plate-like corundum powder, 4-6 parts of kyanite powder and 6-10 parts of silicon carbide powder, the binder is 3-5 parts of calcium aluminate cement, the anti-corrosion agent is composed of 1-2 parts of spherical asphalt, 3-6 parts of zirconium-containing silicon powder and 1-1.6 parts of metallic silicon powder, and the additive is composed of 3-5 parts of alumina powder, 0.1-0.2 parts of polypropylene fiber and 0.15-0.2 parts of sodium tripolyphosphate.

[0009] As an optimization scheme for the above-mentioned refractory castable specially used for industrial silicon refining ladle, the Al2O3 content in the high-quality bauxite homogenous material is not less than 87.8%, the Fe2O3 content is not more than 1.8%, the TiO2 content is 3.0-3.5%, and the bulk density is 3.32-3.40 g / cm 3 , and the apparent porosity is not higher than 4.5%, and it has closed pores.

[0010] As another optimization scheme of the above-mentioned refractory castable specially used for industrial silicon refining ladle, the high-quality bauxite homogeneous material has a corundum main crystal phase, a mullite phase, an aluminum titanate solid solution and an iron titanate solid solution.

[0011] As another optimization scheme for the above-mentioned refractory castable specially used for industrial silicon refining ladle, the high-quality bauxite homogeneous material has four particle gradations, among which the 8-5mm part accounts for 21-25% of the total mass of the bauxite homogeneous material, the 5-3mm part accounts for 28-34% of the total mass of the bauxite homogeneous material, the 3-1mm part accounts for 28-35% of the total mass of the bauxite homogeneous material, and the 1-0mm part accounts for 15-20% of the total mass of the bauxite homogeneous material.

[0012] As another optimization scheme for the above-mentioned refractory castable specially used for industrial silicon refining package, the particle size of the sillimanite particles does not exceed 0.18mm; the fineness of plate-like corundum powder, kyanite powder, silicon carbide powder and metallic silicon powder does not exceed 0.074mm; the particle size of spherical asphalt is 0.3-1mm; the particle size of zirconium silicon micropowder does not exceed 1 micron, and the particle size of alumina micropowder does not exceed 3 microns.

[0013] As another optimization scheme for the above-mentioned refractory castable specially used for industrial silicon refining package, the Al2O3 content in the plate-like corundum powder is not less than 98%, the Al2O3 content in the kyanite powder is not less than 58%, the SiC content in the silicon carbide powder is not less than 98%, the fixed carbon content of the spherical asphalt is not less than 50.5%, and the ash content does not exceed 0.18%; the Al2O3 content in the sillimanite particles does not exceed 57%, and the Fe2O3 content does not exceed 2.0%; the Si content of the metallic silicon powder is not less than 99.5%.

[0014] As another optimization scheme of the above-mentioned refractory castable specially used for industrial silicon refining ladle, the length of the polypropylene fiber is 10-20 mm and the melting point is 165-170°C.

[0015] As another optimization scheme for the above-mentioned refractory castable specially used for industrial silicon refining ladle, the zirconium-containing silicon micropowder is an amorphous SiO2 micropowder collected after cooling the silicon dioxide gas generated during the desiliconization zirconium production process, and the SiO2 content is 94.0-95.0%, and the ZrO2 content is 3.6-4.0%.

[0016] As another optimization scheme for the above-mentioned refractory castable specially used for industrial silicon refining ladle, the calcium aluminate cement is a low-calcium and low-iron calcium aluminate cement with Al2O3 content not less than 69%, CaO content not more than 29%, and Fe2O3 content less than 0.3%.

[0017] A method for preparing a refractory castable specially used for an industrial silicon refining ladle comprises the following steps:

[0018] 1) According to the above weight ratio, weigh each component separately, and divide the silicon carbide powder in the refractory fine powder into two parts according to the mass ratio of 4:6 for standby use;

[0019] 2) The spherical asphalt, zirconium-containing silicon powder and metallic silicon powder constituting the anti-corrosion agent are mixed evenly with the silicon carbide powder having a smaller weight to form powder A;

[0020] 3) Evenly mix the kyanite powder, sillimanite particles and the heavier portion of silicon carbide powder to form powder B;

[0021] 4) The high-quality bauxite homogenized material in the refractory aggregate, the plate-shaped corundum powder in the refractory fine powder, the binder, the admixture, the powder A and the powder B are fully mixed and uniformly mixed to obtain the refractory castable specially used for the industrial silicon refining bag.

[0022] The mechanism of improving the corrosion resistance of the castable of the present invention on components such as Na2O and B2O3 in industrial silicon refining slag is as follows:

[0023] First, the spherical asphalt is evenly dispersed in the castable. Under high temperature, the spherical asphalt gradually carbonizes to fill or block the pores, preventing the slag from penetrating into the castable. On the other hand, the volatile matter in it will gasify. Under the action of gas pressure, the carbon element in the volatile matter enters the tiny pores of the material and forms a carbon coating on the inner wall of the pore, protecting the material from or delaying the erosion of the slag components.

[0024] Secondly, at the oxidation refining temperature, the metallic silicon powder and silicon carbide powder in the surface matrix of the castable can be incompletely oxidized to form SiO, and then react with C in the asphalt to form fibrous silicon carbide (SiC). Moreover, the fibrous silicon carbide can be combined with the aluminum titanate solid solution and the iron titanate solid solution, further improving the corrosion resistance to Na2O and B2O3, and also improving the thermal shock resistance of the castable;

[0025] Finally, zirconium-silicon micropowder can significantly increase the viscosity of the slag liquid even when reacting with the slag liquid and melting into the slag at a high temperature of about 1600°C, thereby significantly improving the resistance of the slag liquid to penetrate and erode into the interior of the castable.

[0026] In addition, considering that the working conditions of silicon ladle are worse than those of steel ladle, the castable of the present invention also has excellent thermal shock resistance, and its improvement mechanism is as follows:

[0027] Although the phase composition of the high-quality bauxite homogeneous material of the present invention is mainly corundum, it contains 3.0-3.5% TiO2, and the preparation process of wet ball milling, spray granulation, pressing into billets, and high-temperature sintering makes it contain a small amount of iron titanate and aluminum titanate solid solution with a very small thermal expansion coefficient and a certain amount of evenly distributed closed pores. This phase composition and microstructure reduce the thermal expansion coefficient and elastic modulus of the corundum bauxite homogeneous material to a certain extent, thereby helping to improve the thermal shock resistance of the castable;

[0028] A certain amount of "kyanite + sillimanite" is introduced into the castable of the present invention, and the mullite and volume effects produced by them in a wide temperature range of about 1100°C to 1700°C are utilized. Firstly, the glass phase material produced in the mullite process can promote the sintering of the material and improve its mechanical strength; secondly, the volume expansion accompanied by mullite can increase the density of the industrial silicon refining lining, which is beneficial to inhibit the erosion of slag into the interior of the lining and improve the slag resistance of the castable; thirdly, when the secondary crystalline phase mullite with a smaller thermal expansion coefficient coexists with the main crystalline phase corundum with a larger thermal expansion coefficient, microcracks will be formed between the grains during the drastic temperature increase and decrease process due to the mismatch of the thermal expansion coefficients of the primary and secondary crystalline phases, thereby increasing the toughness of the material and improving the thermal shock resistance of the material;

[0029] The castable of the present invention constructively uses zirconium-containing silicon powder, and utilizes the volume effect generated when tetragonal zirconium oxide (t-ZrO2) transforms into monoclinic zirconium oxide (m-ZrO2) to reduce the strain generated when the material is subjected to a thermal shock strain field, thereby achieving the effect of improving the thermal shock resistance of the material.

[0030] The castable of the present invention has higher thermal conductivity, which reduces the temperature difference between the inside and outside of the lining during thermal shock. When the material is subjected to thermal shock, thermal stress will be generated due to volume change (expansion or contraction). Excessive thermal stress can easily lead to material damage or even destruction and failure. The magnitude of thermal stress is directly related to the temperature difference between the inside and outside of the material during thermal shock. A certain amount of silicon carbide fine powder and spherical asphalt are used in the castable of the present invention, both of which have relatively high thermal conductivity, which is beneficial to reducing the temperature difference between the inside and outside of the material during thermal shock and improving the thermal shock resistance of the castable.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] Firstly, the present invention constructively adopts a scientific and reasonable material composite toughening technology to significantly improve the thermal shock resistance of the castable; more importantly, the composite use of spherical asphalt, silicon carbide, metallic silicon powder, zirconium-containing silicon powder, etc. effectively improves the corrosion resistance of the castable to components such as Na2O and B2O3 in the slag, thereby achieving a good balance in improving the mechanical strength, slag corrosion resistance and thermal shock resistance of the material, so that the castable has excellent comprehensive performance;

[0033] Secondly, the present invention optimizes the composition and proportion, so that the refractory castable of the present invention has the advantages of good anti-blasting performance, short curing and baking time, low production cost, simple process, easy control of quality process, etc. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. The parts not described in the following embodiments of the present invention are regarded as the prior art known or should be known to those skilled in the art.

[0035] The raw materials used in the following embodiments of the present invention are as follows:

[0036] The high-quality bauxite homogenous material used is a conventional bauxite raw material that is homogenized, wet ball milled, spray granulated, pressed into billets, and sintered at high temperature. The Al2O3 content is not less than 87.8%, the Fe2O3 content is not more than 1.8%, the TiO2 content is 3.0-3.5%, and the bulk density is 3.32-3.40g / cm 3, the apparent porosity is not higher than 4.5%, and it has certain closed pores; in addition to the main crystal phase of corundum, it also contains a small amount of aluminum titanate solid solution and iron titanate solid solution; in addition, high-quality bauxite homogeneous material is composed of four particle gradations, namely: the 8-5mm part accounts for 21-25% of the total mass of the bauxite homogeneous material, the 5-3mm part accounts for 28-34% of the total mass of the bauxite homogeneous material, the 3-1mm part accounts for 28-35% of the total mass of the bauxite homogeneous material, and the 1-0mm part accounts for 15-20% of the total mass of the bauxite homogeneous material. They are reasonably matched with other fine powders to form a close stacking in the castable and improve the volume density of the castable.

[0037] In the test and comparison experiments, the high-quality bauxite homogenous material selected had an Al2O3 content of 89.3%, a Fe2O3 content of 1.2%, a TiO2 content of 3.2%, and a bulk density of 3.38 g / cm 3 , the apparent porosity is 4.1%.

[0038] The sillimanite particles used were ground and sieved to a particle size not exceeding 0.18 mm, with an Al2O3 content of 51.63% and a Fe2O3 content of 1.58%;

[0039] The fineness of the plate-shaped corundum powder, kyanite powder, silicon carbide powder and metallic silicon powder used is no more than 0.074mm, the particle size of the spherical asphalt is 0.3-1mm, and the particle size of the alumina micro powder is no more than 3 microns;

[0040] The Al2O3 content in plate-like corundum powder is 98.83%, the Al2O3 content in kyanite powder is 62.34%, the SiC content in silicon carbide powder is 99.12%, the fixed carbon content of spherical asphalt is 52.69%, and the ash content is 0.12%; the Si content of metallic silicon powder is 99.68%;

[0041] The length of the polypropylene fiber used is 10-20 mm, and the melting point is 165-170°C;

[0042] The zirconium-containing silicon powder used is an amorphous SiO2 powder collected after cooling the silicon dioxide gas generated in the desiliconized zirconium production process, and the SiO2 content is 94.2%, the ZrO2 content is 3.8%, and the particle size does not exceed 1 micron;

[0043] The calcium aluminate cement used is low-calcium, low-iron calcium aluminate cement with an Al2O3 content of 73.2%, a CaO content of 24.7%, and a Fe2O3 content of 0.21%. Example 1

[0044] A refractory castable specially used for industrial silicon refining ladle, comprising refractory aggregate, refractory fine powder, binder, anti-corrosion agent and additives. According to weight ratio, the refractory aggregate is composed of 61 parts of high-quality bauxite homogenate and 2.5 parts of sillimanite particles, the refractory fine powder is composed of 5 parts of plate-shaped corundum powder, 4 parts of kyanite powder and 6 parts of silicon carbide powder, the binder is 3 parts of calcium aluminate cement, the anti-corrosion agent is composed of 1 part of spherical asphalt, 3 parts of zirconium-containing silicon powder and 1 part of metallic silicon powder, and the additive is composed of 3 parts of alumina powder, 0.1 parts of polypropylene fiber and 0.15 parts of sodium tripolyphosphate;

[0045] The preparation method of the above refractory castable comprises the following steps:

[0046] 1) According to the above weight ratio, weigh each component separately, and divide the silicon carbide powder in the refractory fine powder into two parts according to the mass ratio of 4:6 for standby use;

[0047] 2) The spherical asphalt, zirconium-containing silicon powder and metallic silicon powder constituting the anti-corrosion agent are mixed evenly with the silicon carbide powder having a smaller weight to form powder A;

[0048] 3) Evenly mix the kyanite powder, sillimanite particles and the heavier portion of silicon carbide powder to form powder B;

[0049] 4) The high-quality bauxite homogenized material in the refractory aggregate, the plate-shaped corundum powder in the refractory fine powder, the binder, the admixture, the powder A and the powder B are fully mixed and uniformly mixed to obtain the refractory castable specially used for the industrial silicon refining bag. Example 2

[0050] A refractory castable specially used for industrial silicon refining ladle, comprising refractory aggregate, refractory fine powder, binder, anti-corrosion agent and additives. According to weight ratio, the refractory aggregate is composed of 68.5 parts of high-quality bauxite homogenate and 4 parts of sillimanite particles, the refractory fine powder is composed of 8 parts of plate-shaped corundum powder, 6 parts of kyanite powder and 10 parts of silicon carbide powder, the binder is 5 parts of calcium aluminate cement, the anti-corrosion agent is composed of 2 parts of spherical asphalt, 6 parts of zirconium-containing silicon powder and 1.6 parts of metallic silicon powder, and the additive is composed of 5 parts of alumina powder, 0.2 parts of polypropylene fiber and 0.2 parts of sodium tripolyphosphate;

[0051] The preparation method of the above refractory castable comprises the following steps:

[0052] 1) According to the above weight ratio, weigh each component separately, and divide the silicon carbide powder in the refractory fine powder into two parts according to the mass ratio of 4:6 for standby use;

[0053] 2) The spherical asphalt, zirconium-containing silicon powder and metallic silicon powder constituting the anti-corrosion agent are mixed evenly with the silicon carbide powder having a smaller weight to form powder A;

[0054] 3) Evenly mix the kyanite powder, sillimanite particles and the heavier portion of silicon carbide powder to form powder B;

[0055] 4) The high-quality bauxite homogenized material in the refractory aggregate, the plate-shaped corundum powder in the refractory fine powder, the binder, the admixture, the powder A and the powder B are fully mixed and uniformly mixed to obtain the refractory castable specially used for the industrial silicon refining bag. Example 3

[0056] A refractory castable specially used for industrial silicon refining ladle, comprising refractory aggregate, refractory fine powder, binder, anti-corrosion agent and additives. According to weight ratio, the refractory aggregate is composed of 63 parts of high-quality bauxite homogenate and 3 parts of sillimanite particles, the refractory fine powder is composed of 6 parts of plate-shaped corundum powder, 5 parts of kyanite powder and 8 parts of silicon carbide powder, the binder is 4 parts of calcium aluminate cement, the anti-corrosion agent is composed of 1.5 parts of spherical asphalt, 4 parts of zirconium-containing silicon powder and 1.3 parts of metallic silicon powder, and the additive is composed of 4 parts of alumina powder, 0.15 parts of polypropylene fiber and 0.18 parts of sodium tripolyphosphate;

[0057] The preparation method of the above refractory castable comprises the following steps:

[0058] 1) According to the above weight ratio, weigh each component separately, and divide the silicon carbide powder in the refractory fine powder into two parts according to the mass ratio of 4:6 for standby use;

[0059] 2) The spherical asphalt, zirconium-containing silicon powder and metallic silicon powder constituting the anti-corrosion agent are mixed evenly with the silicon carbide powder having a smaller weight to form powder A;

[0060] 3) Evenly mix the kyanite powder, sillimanite particles and the heavier portion of silicon carbide powder to form powder B;

[0061] 4) The high-quality bauxite homogenized material in the refractory aggregate, the plate-shaped corundum powder in the refractory fine powder, the binder, the admixture, the powder A and the powder B are fully mixed and uniformly mixed to obtain the refractory castable specially used for the industrial silicon refining bag. Example 4

[0062] A refractory castable specially used for industrial silicon refining ladle, comprising refractory aggregate, refractory fine powder, binder, anti-corrosion agent and additives. According to weight ratio, the refractory aggregate is composed of 65 parts of high-quality bauxite homogenate and 3.5 parts of sillimanite particles, the refractory fine powder is composed of 7 parts of plate-shaped corundum powder, 5 parts of kyanite powder and 8.5 parts of silicon carbide powder, the binder is 4.5 parts of calcium aluminate cement, the anti-corrosion agent is composed of 1.8 parts of spherical asphalt, 5 parts of zirconium-containing silicon powder and 1.5 parts of metallic silicon powder, and the additive is composed of 4.5 parts of alumina powder, 0.16 parts of polypropylene fiber and 0.17 parts of sodium tripolyphosphate;

[0063] The preparation method of the above refractory castable comprises the following steps:

[0064] 1) According to the above weight ratio, weigh each component separately, and divide the silicon carbide powder in the refractory fine powder into two parts according to the mass ratio of 4:6 for standby use;

[0065] 2) The spherical asphalt, zirconium-containing silicon powder and metallic silicon powder constituting the anti-corrosion agent are mixed evenly with the silicon carbide powder having a smaller weight to form powder A;

[0066] 3) Evenly mix the kyanite powder, sillimanite particles and the heavier portion of silicon carbide powder to form powder B;

[0067] 4) The high-quality bauxite homogenized material in the refractory aggregate, the plate-shaped corundum powder in the refractory fine powder, the binder, the admixture, the powder A and the powder B are fully mixed and uniformly mixed to obtain the refractory castable specially used for the industrial silicon refining bag.

[0068] Comparative experiment:

[0069] 1. Sample preparation

[0070] The products obtained in Examples 1 to 4 were added with an appropriate amount of water and stirred evenly, and then vibrated, cast, molded, and demolded, and then baked at 110° C. for 24 h, and then calcined at 1500° C. for 3 h, and naturally cooled to obtain Samples 1 to 4;

[0071] Comparative Example 1

[0072] Select Al2O3-SiC-C iron trough castable used in existing steel smelting, add appropriate amount of water and stir it thoroughly, then perform vibration casting, molding, demoulding, and then bake at 110℃ for 24 h, and then calcine at 1500℃ for 3 h, and then cool naturally to obtain sample 5;

[0073] Comparative Example 2

[0074] The components of Example 4 were removed from the spherical asphalt and zirconium-containing silicon powder in the anti-corrosion agent component, namely, 65 parts of high-quality bauxite homogenate, 3.5 parts of sillimanite particles, 7 parts of plate-shaped corundum powder, 5 parts of kyanite powder, 8.5 parts of silicon carbide powder, 4.5 parts of calcium aluminate cement, 1.5 parts of metallic silicon powder, 4.5 parts of alumina powder, 0.16 parts of polypropylene fiber and 0.17 parts of sodium tripolyphosphate. These components were directly mixed evenly, added with appropriate amount of water and stirred well, then vibrated and cast, formed, demolded, baked at 110°C for 24 h, calcined at 1500°C for 3 h, and naturally cooled to obtain sample 6;

[0075] Comparative Example 3

[0076] The components of Example 4 are removed from the spherical asphalt in the anti-corrosion agent component, namely, 65 parts of high-quality bauxite homogenate, 3.5 parts of sillimanite particles, 7 parts of plate-shaped corundum powder, 5 parts of kyanite powder, 8.5 parts of silicon carbide powder, 4.5 parts of calcium aluminate cement, 5 parts of zirconium-containing silicon powder, 1.5 parts of metallic silicon powder, 4.5 parts of alumina powder, 0.16 parts of polypropylene fiber and 0.17 parts of sodium tripolyphosphate. These components are directly mixed evenly, added with appropriate amount of water and fully stirred, and then vibrated and cast, formed, demolded, and then baked at 110°C for 24 hours, and then calcined at 1500°C for 3 hours. After natural cooling, sample 7 is obtained;

[0077] Comparative Example 4

[0078] According to the components of Example 4, during the preparation, all the components were directly mixed uniformly to form a casting material, that is, powder A and powder B were not prepared according to the method of step 2) and step 3) in Example 4. The final castable was added with an appropriate amount of water and fully stirred, and then vibrated, cast, molded, and demolded, and then baked at 110°C for 24 hours, and then calcined at 1500°C for 3 hours. After natural cooling, sample 8 was obtained;

[0079] 2. Comparative Experimental Contents:

[0080] 2.1) According to the existing testing methods, the bulk density, flexural strength and compressive strength of samples 1 to 8 were measured respectively. The test results are shown in Table 1;

[0081] 2.2) Anti-corrosion test

[0082] The corrosion resistance test was carried out on samples 1 to 8 respectively, and the corrosion resistance was evaluated by the average thickness of the castable crucible sample corroded by the slag reaction. The test results are shown in Table 1.

[0083] The corrosion resistance test adopts the static crucible method, the experimental conditions are 1580℃×3h, and the slag is industrial silicon smelting slag powder ground to 180 mesh;

[0084] 2.3) Thermal shock resistance test

[0085] Thermal shock resistance tests were conducted on samples 1 to 8 respectively, and the room temperature flexural strength retention rate of the samples after thermal shock was used for evaluation. The greater the flexural strength retention rate, the better the thermal shock resistance of the castable. The test results are shown in Table 1.

[0086] The thermal shock resistance test was conducted at 1000℃×30min→air cooling for 5 times. The slag sample used in the corrosion resistance test was directly industrial silicon smelting slag powder ground to 180 mesh.

[0087]

[0088] Experimental results analysis

[0089] From the test results in Table 1, it can be seen that the flexural strength and compressive strength of samples 1 to 8 are not much different, and the flexural strength retention rate reflects the difference in thermal shock resistance. Although the flexural strength retention rate of samples 5 to 7 (i.e., comparative examples 1 to 3) is slightly worse, lower than that of the present invention (Examples 1-4), the difference is not particularly large;

[0090] As for the index reflecting the corrosion resistance to industrial silicon slag, the average corrosion thickness shows that the corrosion resistance of the castable of the present invention to industrial silicon slag is much better than that of the existing castable for steel smelting (the average corrosion thickness of samples 1-4 is about 1.0, while the average corrosion thickness of sample 5 has reached 3.5). As for samples 6 and 7, because of the different anti-corrosion agent components contained therein, their corrosion resistance effect is also worse than that of the present invention (the average corrosion thickness of samples 6 and 7 is above 2.1). As for sample 8, although the anti-corrosion agent component is the same as that of sample 4, the castable of sample 8 is made by directly mixing the components evenly, while sample 4 is made by mixing the components evenly. The steps 1-4 of the preparation method of the present invention are strictly followed. There are differences in the preparation methods of the two, which leads to the poorer corrosion resistance of sample 8 than that of sample 4 (the average corrosion thickness of sample 8 is 1.3 mm, while that of sample 4 is only 0.7 mm). This also proves from the side that the method of the present invention firstly mixes the raw materials constituting the corrosion inhibitor, zirconium-containing silicon micropowder, metallic silicon powder and part of silicon carbide to form powder A, then mixes kyanite powder, sillimanite particles and another part of silicon carbide to form powder B, and finally makes the remaining ingredients into a castable with powder A and powder B. Compared with the existing method of directly mixing all the ingredients, the method can better prevent the corrosion of industrial silicon slag.

Claims

1. A refractory castable for industrial silicon refining ladle, comprising refractory aggregate, refractory fine powder, binder, anti-corrosion agent and admixture, characterized in that: According to the weight ratio, the refractory aggregate is composed of 61-68.5 parts of high-quality bauxite homogenous material and 2.5-4 parts of sillimanite particles, the refractory fine powder is composed of 5-8 parts of plate-shaped corundum powder, 4-6 parts of kyanite powder and 6-10 parts of silicon carbide powder, the binder is 3-5 parts of calcium aluminate cement, the anti-corrosion agent is composed of 1-2 parts of spherical asphalt, 3-6 parts of zirconium-containing silicon powder and 1-1.6 parts of metallic silicon powder, the admixture is composed of 3-5 parts of alumina powder, 0.1-0.2 parts of polypropylene fiber and 0.15-0.2 parts of sodium tripolyphosphate; the Al2O3 content in the high-quality bauxite homogenous material is not less than 87.8%, the Fe2O3 content is not more than 1.8%, the TiO2 content is 3.0-3.5%, and the bulk density is 3.32-3.40 g / cm 3 , and the apparent porosity is not higher than 4.5%, and it has closed pores; the high-quality bauxite homogeneous material has a corundum main crystal phase, a mullite phase, an aluminum titanate solid solution and an iron titanate solid solution; the zirconium-containing silicon micropowder is an amorphous SiO2 micropowder obtained by collecting the silicon dioxide gas generated during the desiliconization zirconium production process after cooling, and the SiO2 content is 94.0-95.0%, and the ZrO2 content is 3.6-4.0%.

2. A refractory castable for industrial silicon refining ladle according to claim 1, characterized in that: The high-quality homogeneous bauxite material has four particle gradations, among which the 8-5mm part accounts for 21-25% of the total mass of the homogeneous bauxite material, the 5-3mm part accounts for 28-34% of the total mass of the homogeneous bauxite material, the 3-1mm part accounts for 28-35% of the total mass of the homogeneous bauxite material, and the 1-0mm part accounts for 15-20% of the total mass of the homogeneous bauxite material.

3. A refractory castable for industrial silicon refining ladle according to claim 1, characterized in that: The particle size of the sillimanite particles does not exceed 0.18mm; the fineness of plate-shaped corundum powder, kyanite powder, silicon carbide powder and metallic silicon powder does not exceed 0.074mm; the particle size of spherical asphalt is 0.3-1mm; the particle size of zirconium-containing silicon micropowder does not exceed 1 micron, and the particle size of alumina micropowder does not exceed 3 microns.

4. A refractory castable for industrial silicon refining ladle according to claim 1, characterized in that: The Al2O3 content in the plate-like corundum powder is not less than 98%, the Al2O3 content in the kyanite powder is not less than 58%, the SiC content in the silicon carbide powder is not less than 98%, the fixed carbon content of the spherical asphalt is not less than 50.5%, and the ash content does not exceed 0.18%; the Al2O3 content in sillimanite does not exceed 57%, and the Fe2O3 content does not exceed 2.0%; the Si content of the metallic silicon powder is not less than 99.5%.

5. The refractory castable for industrial silicon refining ladle according to claim 1, characterized in that: The length of the polypropylene fiber is 10-20 mm, and the melting point is 165-170° C.

6. A refractory castable for industrial silicon refining ladle according to claim 1, characterized in that: The calcium aluminate cement is a low-calcium, low-iron calcium aluminate cement with an Al2O3 content of not less than 69%, a CaO content of not more than 29%, and a Fe2O3 content of less than 0.3%.

7. A method for preparing a refractory castable for an industrial silicon refining ladle according to any one of claims 1 to 6, characterized in that: The steps include: 1) According to the weight ratio described in any one of claims 1 to 6, weigh each component respectively, and divide the silicon carbide powder in the refractory fine powder into two parts according to the mass ratio of 4:6 for standby use; 2) The spherical asphalt, zirconium-containing silicon powder and metallic silicon powder constituting the anti-corrosion agent are mixed evenly with the silicon carbide powder having a smaller weight to form powder A; 3) Evenly mix the kyanite powder, sillimanite particles and the heavier portion of silicon carbide powder to form powder B; 4) The high-quality bauxite homogenized material in the refractory aggregate, the plate-shaped corundum powder in the refractory fine powder, the binder, the admixture, the powder A and the powder B are fully mixed and uniformly mixed to obtain the refractory castable specially used for the industrial silicon refining bag.

Citation Information

Patent Citations

  • Homogenized material-containing blast furnace tapping yard branch channel castable and preparation method thereof

    CN104761269A

  • Castable for reducing atmosphere kiln

    CN109503181A